2020
DOI: 10.1097/iae.0000000000002556
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Choriocapillaris Impairment in Eyes With Choroidal Neovascularization Secondary to Age-Related Macular Degeneration

Abstract: Purpose: To develop an optical coherence tomography angiography (OCTA)-based framework for quantitatively analyzing the spatial distribution of choriocapillaris (CC) impairment around choroidal neovascularization (CNV) secondary to age-related macular degeneration. Methods: In a retrospective, cross-sectional study, 400-kHz swept-source OCTA images from 7 eyes of 6 patients with CNV secondary to age-related macular degeneration were quantitatively analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Recent advances in OCTA and image analysis techniques 36 have demonstrated that CC impairment is greatest in the region surrounding MNV, but these studies were small and descriptive. 1 , 19 , 33 , 37 Recent work by Treister et al 16 best parallels the current analysis described in this article. The Treister study included FD% in the DH itself (defined as a 200 µm ring around the MNV) 16 and noted a greater CC FD% in the halo, as would be expected.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Recent advances in OCTA and image analysis techniques 36 have demonstrated that CC impairment is greatest in the region surrounding MNV, but these studies were small and descriptive. 1 , 19 , 33 , 37 Recent work by Treister et al 16 best parallels the current analysis described in this article. The Treister study included FD% in the DH itself (defined as a 200 µm ring around the MNV) 16 and noted a greater CC FD% in the halo, as would be expected.…”
Section: Discussionsupporting
confidence: 65%
“…The process of macular neovascularization (MNV) secondary to AMD can be associated with significant disruption of the choriocapillaris (CC) in the area surrounding the MNV 1 , 2 and CC impairment may be the initial insult that drives MNV formation, suggesting that neovascular AMD may be a vascular disease with secondary RPE and photoreceptor degeneration owing to CC damage. 1 , 3 , 4 Recent optical coherence tomography angiography (OCTA) studies have shown that eyes with geographic atrophy exhibit greater CC flow deficits (FD) versus normal eyes and versus eyes with neovascular AMD and that CC impairment may predict the progression of geographic atrophy (GA). 5 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This dark halo may in fact be a marker of activity of the neovascularization [ 78 , 98 ]. The choriocapillaris immediately surrounding MNV shows higher flow deficits than other areas of the macula [ 109 , 110 , 111 ]. The association holds true even when analyzing only the choriocapillaris immediately outside of the perilesional dark halo in treatment-naïve eyes ( Figure 4 ) [ 44 ].…”
Section: Octa Of the Choriocapillaris In Neovascular Amdmentioning
confidence: 99%
“…Studies have shown that levotinib is effective in the treatment of anti-angiogenesis. It can inhibit angiogenesis by inhibiting the activation of VEGF2R, suggesting that levotinib may also be effective in the treatment of fundus angiogenesis-related diseases ( Farinha et al, 2020 , Moult et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%